Market Entry Strategy of Porsche AG to China - Souza Alcantara, Bruno (2021)
The goal of this thesis is to identify, how Porsche AG entered mainland China and the niche arguments for the strategy which the company has been using since its market entry, until the recent years, through a case study. There are three chapters. The first one starts with the theoretical study, analyzing and describing the international marketing framework, related to the international market entry process. In the second chapter, the company Porsche AG was introduced, and its expansion process to mainland China was studied. The marketing tools to analyze the Chinese market were then applied to the case study, such as the macro and micro environment analysis, SWOT, and PEST analysis. Recent information about the conditions for the company in China was also analyzed. Lastly, the key findings from the research were listed, where some recommendations for the entry mode in the automobile industry were given, based on the identification of the Chinese market and the Porsche case.